Imaging and neuropathological findings in patients with Post COVID-19 Neurological Syndrome—A review - Okrzeja, Jakub; Garkowski, Adam; Kubas, Bożena; Moniuszko-Malinowska, Anna (Frontiers in Neurology, 2023)
Post COVID-19 syndrome is determined as signs and symptoms that appear during or after an infection consistent with SARS-CoV-2 disease, persist for more than 12 weeks and are not explained by an alternative diagnosis. This review presents the neuropathological findings and imaging findings in Post COVID-19 Neurological Syndrome: the focal point is on the manifestations of involvement evident on brain and spine imaging.